The Coordination Of Actors In Urban Regeneration Projects: Fikirtepe, Istanbul, Turkey - TUBA SARI HAKSEVER; CANDAN ÇINAR ÇITAK (Journal of Contemporary Urban Affairs, 2019)
It is necessary for urban regeneration projects to be carried out successfully in coordination with other actors. During the process of realising regeneration, many actors and strategically-given decision play a crucial role. The ways how actors/factors are involved in the process, the relationships founded among them and investigating the methods followed during the process constitute the content of this study. The purpose of this study is to develop an approach with regard to the coordination established between actors/factors that participated during the regeneration process. This study covers the regeneration activities realised in Fikirtepe and its surrounding area, and it aims to solve the relationships among the actors during the time of planning and applications by using the semi-structured technique, one of the qualitative research methods, and detailed interviews. Thanks to the data gained from the effectiveness of the detailed interview of the actors have been determined.  By the help of the findings obtained from Fikirtepe region, the relationships and coordination among the actors have been revealed and a new approach has been created (and suggested) concerning the effectiveness and coordination.